The Effect Of Giving Date Juice On Hemoglobin Levels of Pregnant Women In The Third Trimester Anemia at Pratama Clinic Hanum Medan 2020 - Riska Maulidanita; Ainun Mardiah (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2021)
Background: Anemia is a state when hemoglobinlevels, hematocrit and erythrocyte amounts fall below normal values. Anemia generally occurs throughout the world, especially in developing countries and in low-income socio-economic groups. Purpose: The research method used is a quasi experimental experiment with a pre-experimental form, One Group Pre- Test-Post Test. The research population is all pregnant women in the third trimester at The Pratama Hanum Medan clinic as many as 20 people. Sampling technique using purpose sampling as many as 15 people. Result: Showed that the average hemoglobin level of respondents who were anemic before being given date juice was 9.467 gr / dL. The lowest hemoglobin level is 9.0 gr/dL and the highest is 10.0 gr/dL. The average hemoglobin level of respondents who were anemic after being given date juice was 11.333 gr/dL. The lowest hemoglobin level is 11.0 gr/dL and the highest is 11.8 gr/dL. Based on the results of the T-test test obtained p value = 0.000. Conclusion: This study is that there is an effect of giving date juice on hemoglobin levels in pregnant women in trimester III who have anemia at The Pratama Hanum Medan Clinic in 2021, where hemoglobin levels with a value of p value = 0.000.